New source number estimation algorithm based on l 1 sparse regularization - Fang-xiao JIN; Tian-shuang QIU; Peng WANG; Nan XIA; Jing-chun LI (Tongxin xuebao)
In view of the problems of inefficient in low SNR and less snapshots when using existing sources number estimation related algorithms,a new algorithm based on e1sparse regularization under space stationary noise was proposed to estimate the number of signal sources.The algorithm estimated the sources number by using the sparse representation of eigenvalues vectors with the suitable regularization parameter.Theoretical analysis and simulation results show that the algorithm can realize an accurate sources number estimation in low SNR and less snapshots.